Production And Characterization Of Poly(3-Hydroxybutyrate-Co-4-Hydroxybutyrate) Copolymer - Ahmad, Rahayu (2011)

(untitled)
A locally isolated Cupriavidus sp. USMAA2-4 possessing the ability to produce biodegradable polymer was used in this study to explore the production of biopolymer through one-stage cultivation process and fed-batch fermentation. Various palm oilbased carbon sources, fatty acids and its combination were used for producing high cell dry weight of Cupriavidus sp. USMAA2-4. Utilization of oleic acid solely yielding the highest cell dry weight with 8.4 g/L. Effects of carbon to nitrogen (C/N ratio) on the accumulation of P(3HB) before feeding of carbon precursor (γ-butyrolactone) exhibited significant increased of 4HB compositions from 9 to 55 mol% when C/N ratio decreased from 20-8. The monomer composition of 4HB also varied from 4 to 55 mol% when alkanediols with even carbon numbers such as 1,4-butanediol, 1,6-hexanediol, 1,8- octanediol, 1,10-decanediol and 1,12-dodecanediol were used. Feeding strategy of interval feeding time could increased the cell dry weight up to 30 and 31.1 g/L according to 12 and 6 h interval of feeding time respectively, but the 4HB compositions unable to be varied. Feeding of C/N 5 at growth phase and supplementing different concentrations of γ-butyrolactone in accumulation phase using DO-stat method had successfully produced various 4HB compositions ranging from 35 to 68 mol% with the cell dry weight increased up to 14.9 g/L.